A Study of Company Employees’ Satisfaction, Knowledge, and Perception of Tax Benefits Related to Online Personal Income Tax Filing in Lat Krabang District - เจริญสุข ภคมน; มหาสุด พิชญดา; อุสันเทียะ อรจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to: 1) examine the level of satisfaction among company employees in the Lat Krabang district regarding the filing of personal income tax via the internet; and 2) investigate whether demographic characteristics—such as gender, age, educational level, marital status, job position, and department—affect their satisfaction levels. The research employed a survey research design. The sample consisted of 100 company employees in the Lat Krabang district who filed their personal income tax online, with the sample size determined based on the guideline by Hair et al. (2011), which states that survey research in a limited geographic area can use a sample size between 50–100 participants. The sample was selected using purposive sampling to align with the study’s objectives. Data were collected using a questionnaire and analyzed with t-tests and one-way analysis of variance (One-way ANOVA). The results revealed that overall employee satisfaction with online tax filing was at a high level. Satisfaction was measured across two dimensions: information quality (mean = 3.54) and system quality (mean = 3.45), with information quality receiving higher satisfaction ratings. Furthermore, there were no statistically significant differences in satisfaction across demographic groups, including gender, age, educational level, marital status, job position, and department. The findings suggest that the online tax filing system’s accessibility, convenience, reliability, and ability to operate independently at any time and location have contributed to a standardized and equitable service experience for users.